2021
DOI: 10.3136/fstr.27.537
|View full text |Cite
|
Sign up to set email alerts
|

Subtilisin NAT, a subtilisin-like serine protease present in fermented soybean “natto” extract, inhibits <i>Streptococcus mutans</i> biofilm formation

Abstract: Our previous study indicated that the water-soluble extract obtained from commercially available natto products inhibited the sucrose-dependent cariogenic biofilm formation of Streptococcus mutans. This inhibitory effect correlated with the protease activity levels of the extract. Subtilisin NAT (nattokinase), a subtilisin-like serine protease, is a dominant protease found in natto products. In this study, we investigated the effect of natto products produced by a subtilisin NAT-deficient mutant (aprN − ) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Fermented soybean natto produced using this strain as a starter contains abundant proteases, among which nattokinase is the major one [ 25 ]. The protease activity at the concentration of nattokinase used in this study (final concentration 1 mg/mL) was equivalent to that of 10 g wet weight of natto product [ 8 ]. Nattokinase is essentially safe when administered at the recommended dose (200 mg/d); histopathological examination of the organs and tissues have shown no evidence of toxicity [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fermented soybean natto produced using this strain as a starter contains abundant proteases, among which nattokinase is the major one [ 25 ]. The protease activity at the concentration of nattokinase used in this study (final concentration 1 mg/mL) was equivalent to that of 10 g wet weight of natto product [ 8 ]. Nattokinase is essentially safe when administered at the recommended dose (200 mg/d); histopathological examination of the organs and tissues have shown no evidence of toxicity [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that natto, an unsalted fermented soybean food produced using Bacillus subtilis var. natto as a starter, inhibited S. mutans biofilm formation, and the inhibitory factor was nattokinase (subtilisin; EC 3.4.21.62) [ 7 , 8 ], which is a major extracellular enzyme produced by B. subtilis var. natto [ 9 ] and a subtilisin-like alkaline serine protease that exhibits potent thrombolytic activity and substrate specificity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation